Intended and Unintended Effects of Unconditional Cash Transfers: The Case of Bolivia's Renta Dignidad - Werner Hernani-Limarino; Gary Mena (Inter-American Development Bank (IDB), 2015)
This document presents a quasi-experimental impact evaluation of Bolivia's Renta Dignidad, a universal and non-contributory old age pension. Causal effects on direct, future, and indirect beneficiaries are identified, taking advantage of a reduction in age of eligibility from 65 to 60 years in December 2007. Difference-in-difference and changes-in-changes approaches are used to calculate average and quantile treatment effects. For women, non-contributory pensions have, on average, increased their households' non-labor income. This has decreased their labor supply and labor earnings, in turn decreasing households' labor income and thus reducing, ceteris paribus, the program's effect on total per capita household income. Unexpectedly, the program did not have significant effects on men's welfare, investments and labor market outcomes. The results also suggest that additional resources were neither consumed nor invested in health, education, or the purchase of durables. Households most likely held the additional resources and invested in dwelling improvements.
hdl:11319/7350
Keywords: I38; J14; J22; J26; 330; Non-contributory pensions; Well-being; Investment; Saving; Labor market